Hubungan Malaysia-Singapura : Kemungkinan percantuman semula - Jose, Tungak (Universiti Malaysia Sarawak (UNIMAS), 1997)
The aim of this research is to find out the possibility of Singapore joining Malaysia. The issue was raised when Singapore Senior Minister, Lee Kuan Yew, made a statement about the matter in early July 1996. For the issue to become into reality concerning Lee's statement, bilateral relationship between the two countries should be seen from various aspects such as history, politic, economy, cultural and defence system. This was aimed to study all the factors favourable for Singapore to join Malaysia. Library research is used for it is the most suitable method to record all the historical facts and current issues. Based on all the facts surveyed, it is almost impossible for Malaysia and Singapore to reinstate. This facts began from historical factors when Singapore was administered separately as "Crown Colony" within the Malay States. Another history factor is the issue of Singapore joining The Malaysia Federation on 16 September 1965, where it was causes by the dangerous situation then. Subversive Communist activities contributed to the decision of included Singapore into Malaysia. By that time the condition was seen very dangerous for both states if Singapore did not joined Malaysia. Relationship between Malaysia- Singapore is filled with confrontation such as politic, economic, social, cultural and defence. Such situation could be seen when Singapore was in Malaysia (1963-1965). Consequently, the separation of Singapore was inevitable. After the separation of Singapore, bilateral relationship between the two countries often filled with anxiety, distrust and tension especially when both countries compete with each other in different development plan. Thus, the reinstate of both countries may not occur in this nearly time.